2023
DOI: 10.1126/sciadv.ade6561
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent plasticity of gustatory insular cortex circuits and taste preferences

Abstract: Early experience with food influences taste preference in adulthood. How gustatory experience influences development of taste preferences and refinement of cortical circuits has not been investigated. Here, we exposed weanling mice to an array of taste solutions and determined the effects on the preference for sweet in adulthood. We demonstrate an experience-dependent shift in sucrose preference persisting several weeks following the termination of exposure. A shift in sucrose palatability, altered neural resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…It is important to note that repeated exposure to specific beverages or foods can lead to the strengthening or weakening of neural connections between various brain regions involved in taste perception, including the cortex, brainstem, thalamus, and taste receptors. These changes in neural connections can ultimately impact taste preferences. …”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that repeated exposure to specific beverages or foods can lead to the strengthening or weakening of neural connections between various brain regions involved in taste perception, including the cortex, brainstem, thalamus, and taste receptors. These changes in neural connections can ultimately impact taste preferences. …”
Section: Resultsmentioning
confidence: 99%
“…Therapies such as mindfulness-based cognitive therapy might help to improve elementary aspects of the self such as the SSS and consequently act upon higher-order self-components, such as autobiographical memory. Furthermore, recent studies in rodents demonstrated how the IC is plastic [ 202 , 203 , 204 , 205 , 206 ], thus opening new perspectives of treatments, such as repetitive transcranial magnetic stimulation, that our team is currently experimenting in DLB to explore the insula’s different roles (STIMLEWY study). By identifying self-impairments and their anatomical substrates in DLB, we could use the same methods to improve self-awareness, and also more broadly global cognition, sensory abilities and even emotional states.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages offered by GC as a model for studying plasticity 33,38,39 and its well-demonstrated role in conditioned taste aversion 33,36 , familiarity learning 40,41 and associative learning 32,42,43 , few studies have investigated GC’s involvement in taste discrimination learning. Work in rodents has shown that lesions of GC impact salt discrimination learning, confirming a role for this region in this process 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgeries were performed as previously described 13,38,42 . Mice were anesthetized with a cocktail of ketamine (70 mg/kg) and dexmedetomidine (1 mg/kg) administered via intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation